Integrated Monitoring and Assessment Framework of Regional Ecosystem under the Global Climate Change Background - Qiao Wang; Peng Hou; Feng Zhang; Changzuo Wang (Advances in Meteorology)
Global changes are driving ecosystem alterations, and the effects are becoming more and more obvious. Ecosystem management clarifies the fundamental supporting functions of ecosystems for human survival and sustainable development. Integrated ecosystem monitoring and assessment has become a popular topic of ecology study. However, many scientific questions need to be addressed, including what assessment contents and methods are optimal for temporal and spatial measurements. Therefore, the development of a scientific evaluation framework that includes certain core contents and indicators is very important. This paper proposes a regional integrated ecosystem assessment framework involving comprehensive monitoring. Satellite images are the main data source for different ecosystem and ecological parameters, and these need to be supplemented with the help of surveys or field observation data. A healthy ecosystem is the basis of human survival and sustainable development, and ecological service should be taken as the core of integrated ecosystem assessment. This is decided by the spatial distribution, classification, and patterns of regional ecosystems. That is to say, ecological service, together with ecosystems distribution and pattern, ecological problem indicators, and ecological stress, needs to be integrated analyzed and evaluated.